In-situ carbonization of zeolitic imidazolate framework-67 on Ni foam as binder-free electrode for energy storage. (15th December 2022) - Huang, Hsiao-Wen; Hsiao, Yu-Cheng; Chen, Tzu-Yang; Yougbaré, Sibidou; Lin, Lu-Yin; Wu, Yung-Fu
Abstract: Zeolitic imidazolate framework-67 (ZIF67) derivatives are intensively applied as the active material of battery supercapacitor hybrids (BSH) as clean renewable energy. Binder-free electrodes without insulated binders possessing high electrical conductivity can be fabricated with less time and money. In this work, carbonized ZIF67 (C-ZIF67) is fabricated on Ni foam using in-situ binder-free technique. The C-ZIF67 electrode is applied as battery-type electrode of BSH for the first time. Using Ni foam as a conductive substrate of binder-free electrodes is beneficial for generating nickel compounds with multiple redox states. The electrocapacitive nitrogen-doped carbon can be generated from ZIF67 after thermal treatments. Carbonization temperature for synthesizing C-ZIF67 electrodes is optimized regarding morphology and defect to graphitic intensity ratios of C-ZIF67. The C-ZIF67 electrode prepared using 600 °C presents the highest specific capacitance (CF ) of 914.0 F/g along with capacity of 126.9 mAh/g at 20 mV/s, due to tightly attached active material with favorable vertical grown sheet array on Ni form and suitable defect to graphitic intensity ratio. A BSH composed of reduce graphene oxide negative electrode and carbonized ZIF67 positive electrode presents a maximum energy density of 15.15 Wh/kg at 600 W/kg, and the CF retention of 71% and Coulombic efficiency higher than 85% after 6000 charge/discharge cycles. Highlights: A binder-free electrode with the carbonized ZIF67 on nickel foam is fabricated. Effects of carbonization temperature for making carbonized ZIF67 are discussed. Optimal carbonized ZIF67 shows specific capacitance (CF ) of 914.0 F/g at 20 mV/s. BSH with carbonized ZIF67 shows maximum energy density of 15.15 Wh/kg at 600 W/kg. BSH shows a CF retention of 71 % and Columbic efficiency of 85 % after 6000 cycles.